1979
DOI: 10.1037/0022-3514.37.6.865
|View full text |Cite
|
Sign up to set email alerts
|

Vocal interruptions in dyadic communication as a function of speech and social anxiety.

Abstract: Interruptions have been defined as a breach of the "turn-taking" contract in interpersonal communication. The relation between a speaker's personality and his or her propensity to interrupt was examined in 30-min unstructured conversations for 36 dyads (12 male, 12 female, and 12 mixed sex). The following predictions were made: (a) Interruptive behavior is inversely related to speech anxiety and positively related to confidence as a speaker; (b) interruptive behavior is inversely related to social anxiety (avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 31 publications
4
55
0
Order By: Relevance
“…And finally, I would like to argue that overlapped and interrupted talk in POTTI are clear measures of a willingness to actively co-construct the unfolding discourse and not, as has been remarked elsewhere, simply signals of power and dominance. This stance is consistent with conclusions reached by Meltzer, Morris, and Hayes 1971;Gallois and Markel 1975;Natale, Entin, and Jaffe 1979). Other research suggests that these phenomena are culturally determined and dependent; for example, White (1989) investigates in the context of Japanese and interculturally in Japanese/American exchanges and finds significant differences in linguistic behaviour.…”
Section: Engaged Listenershipsupporting
confidence: 79%
“…And finally, I would like to argue that overlapped and interrupted talk in POTTI are clear measures of a willingness to actively co-construct the unfolding discourse and not, as has been remarked elsewhere, simply signals of power and dominance. This stance is consistent with conclusions reached by Meltzer, Morris, and Hayes 1971;Gallois and Markel 1975;Natale, Entin, and Jaffe 1979). Other research suggests that these phenomena are culturally determined and dependent; for example, White (1989) investigates in the context of Japanese and interculturally in Japanese/American exchanges and finds significant differences in linguistic behaviour.…”
Section: Engaged Listenershipsupporting
confidence: 79%
“…And finally, the third perspective views interruption as a positive device as it has the potential to indicate 'heightened involvement' in medial positions within talk (Gallois andMarke 1975). Meltzer (1971), observes that interruptions are not necessarily 'battles for ascendancy ' and Natale et al (1979) However, I also agree with Murray's (1988: 115) observations that 'interruption is always an interpretation -by interactants as well as by analysts -of the intent of a second speaker'. Unfortunately research in this area focussing on dominance or gender has often led to sensationalist claims.…”
supporting
confidence: 56%
“…Murray (1987) finds that women are capable of more interruption and this is corroborated by Bilous and Krauss (1988) for single but not mixed gender dyads. The second vein of study examines issues of culture (see White 1997citing Halmari 1993and Graham 1985, intelligence (Rim 1977), confidence and anxiety Natale et al (1979) correlates of interruption. And finally, the third perspective views interruption as a positive device as it has the potential to indicate 'heightened involvement' in medial positions within talk (Gallois andMarke 1975).…”
mentioning
confidence: 99%
“…Research on interruptions has generally shown that men interrupt women much more often than women interrupt men (Argyle et al, 1968;Eakins and Eakins, 1978;Kester, in Kramer;Natale et al, 1979;Octigan and Niederman, 1979;Zimmerman and West, 1975). Zimmerman and West felt that the differences among cross-sex dyads were reflections of the power and dominance enjoyed by men in society, and in a subsequent study (West and Zimmerman, 1977) found the same sort of marked asymmetry in rates of interruptions among adult-child dyads, thereby giving further credence to the idea that the differences were tied to status.…”
Section: Conversational Division Of Labormentioning
confidence: 94%